BUDGETING AND THE SALES QUOTA. - Drucker, A. P. R. (The Accounting Review, 1929)
For years the system of setting up a budget at the beginning of the fiscal period has been urged upon business conceits, as of September 1929. For a long time the advantages of the budget have been explained to all those who showed the least interest in the subject. Business men were told that the budget system would render a great service to the business in the fact that budgeting requires planning ahead. They were also told that the budget is the best help in coordinating all the activities of the various departments and the budget can be used as a means for centralized executive control. But in spite of all these arguments in its favor, the budget has never appealed strongly to the business executive. After a few years of experimentation with it, they came to the conclusion that it was not worth the money and the effort spent on it. Budgeting, these businessmen claimed, was nothing but guesswork. In addition these business men claim that the budget is after all no help to management as an instrument of control. For everyone in the concern very likely knows that the budget was a compilation of guesses and therefore could not be used as a standard.